Idiopathic osteosclerosis of the jaws on panoramic radiograpic analysis in Indonesian Sub-Population - Irfan Sugianto; Barunawaty Yunus; Fadhlil UA. Rahman; Muliaty Yunus; Dwi P. Wulansari; Muhammad F. Hidayat (Journal of Dentomaxillofacial Science, 2022)
Objective: To determine prevalence of Idiopathic osteosclerosis (IO) by radiographic evaluation and to investigate the relationship between the finding in relation with age, gender and location in Indonesia Sub-Population. Material and Methods: this was a cross-sectional study that panoramic radiograph of patients (1030 male and 1914 female) whose age range 10-82 years old and who visited Department of Oral and Maxillofacial Radiology Hasanuddin University Dental Hospital from 2017 and 2020. We evaluated group of age, location, appearance and occurrence of IO and analyzed using chisquare test. Results: in total, 2944 panoramic radiographs were examined, IO found in 144 (4.8%) patients and 170 IO’s were detected. IO detected mostly in mandible than maxilla (p<0.005) where premolar and molar area was the most common location of IO (42.3% and 41.7%; respectively). Most of cases was solitary lesion (<0.005) and unilateral (<0.005). In addition, most of IO separate from teeth (45.8%) and also related with periapical site (35.3%). Conclusion: Idiopathic Osteosclerosis can defined as developmental variation that can occur in any age range, no predilection of sex. The frequency of IO in Indonesia Sub-population is slightly lower than other country